Securidaca marajoara (Polygalaceae), a new species from the Brazilian Amazon - Silva Da Costa, Christiane; Andrade De Aguiar-Dias, Ana Cristina; Olmos Simões, André (Phytotaxa, 2013)
A new species of the Polygalaceae from the Brazilian eastern Amazon, Securidaca marajoara, is described and illustrated herein. The species is morphologically similar to S. bialata but distinct on the large, conspicuous bracts persistent at flower anthesis, long inflorescences, ovate to elliptic leaves and short internodes.